Health Belief Model Effect on Nurses Hand Hygiene Adherence - Sri Lestari Ramadhani Nasution; Tan Suyono; Adrian Khu; Hans Pangestu Simarmata; Happy Happy (CV. Inara, 2023)
Healthcare acquired infections/HAIs (nosocomial infection) is a growing problem in developing and developed country around the world and one of the contributing factors in the increasing of morbidity, mortality and cost of treatment in hospital. One way to prevent HAIs is by increasing adherence of hand hygiene practice in healthcare workers, including nurses, especially in rooms with high risk of HAIs incidents. This study aims to understand the effect of health belief model (HBM) on the adherence of hand hygiene practice of nurses in rooms with high HAIs risk. A total number of 170 nurses who worked in high HAIs risk enrolled in this study. All nurses then asked to fill questionnaire which consist of demographic factors, experience, personal beliefs, cue to action, and self-efficacy. During this study, all nurses hand hygiene practice also observed directly by researcher. This study found that demographic factor, personal belief, cue to action and self-efficacy have no significant relationship with hand hygiene practice adherence (p>0.05), whilst modifying factor like experience shown to have significant relationship with adherence of hand hygiene practice (p<0.05). Demographic factor, personal belief, cue to action, and self-efficacy component of HBM can’t predict the adherence of hand hygiene practice. However, modifying factor in HBM such as experience can predict the adherence of hand hygiene practice.